Photocatalytic destruction of methyl orange by titanium dioxide powder synthesized by an oxalate co-precipitation method - Pookmanee P. (2014)
Titanium dioxide powder was synthesized by an oxalate co-precipitation method with titanium isopropoxide and oxalic acid as the starting precursors. White precipitate was obtained after adding ammonium hydroxide until the final pH of solution was 8 and then calcined at 400-800 °C for 2h. The phase was characterized by X-ray diffraction. Single phase anatase structure was obtained after calcination at 400°C. Multi-phase of anatase and rutile structure was obtained after calcined at 600 and 800°C. The morphology was investigated by scanning electron microscopy. The particle was irregular in shape and highly agglomerate with a range of particle size from 0.1-0.3 μm. The photocatalytic destruction of methyl orange by titanium dioxide was determined by Ultraviolet spectrophotometry. Titanium dioxide powder synthesized by an oxalate co-precipitation method after calcination at 800°C showed the highest photocatalytic activity. © (2010) Trans Tech Publications.